Plasma-sprayed bovine hydroxyapatite coatings - (:unkn) unknown (ELSEVIER SCIENCE BV, 2004)
With the increase in the life expectancy of humans, the maintenance of bone in our bodies has become crucial. Allografts extracted from different human and bovine sources bring the problem of potential disease transmittal, particularly the transmittal of disease that are difficult to detect. Autogen grafts bring another problem in surgery because the bone harvesting procedure creates cause for an additional surgery. In this study, the hydroxyapatite (HA) material was produced from bovine bones with the calcination method prohibits the transmission of various disease like mad cow disease (bovine spongiform encephalopathy (BSE)). In this study, the calcinated powder was used as plasma feeding powder for the plasma spraying process in biomedical applications. In industrial applications, the use of bond-coating prevents thermal coefficient mismatching and usually results in a stronger material. However, it was seen than bovine hydroxyapatite (BHA) was so strong that it does not need any bond-coating application. Nonetheless, bond-coating can be used to prevent the formation of micro-cracks. BHA material produced with the calcination method can be a very economic biomaterial for plasma spraying purposes when compared to other commercially available biomaterials. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: bovine derived hydroxyapatite; plasma spraying; bond-coating; economic; REINFORCED HYDROXYAPATITE; TITANIUM